Article Classification Using Convolutional Neural Network (CNN) And Chi-Square Feature Selection (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
News articles are reports or information about events that are actual, reliable, and based on facts or reality. The increase in internet users has resulted in the growth of the amount of available information increasing rapidly. Easy internet access makes many types of Indonesian news articles published digitally. With a very large number of news articles, it will be easier to find a news article if the news has been organized and has been grouped according to its respective categories. Text classification is a problem that aims to determine the topic or theme of a document. In achieving this goal, the classification process forms a model that can distinguish data into different classes based on certain rules. The method used to build the model is Convolutional Neural Network (CNN) with Chi-Square feature selection. News articles are divided into six classes, namely news, technology, football, health, lifestyle, and automotive. In this study, the best CNN model was obtained with the number of filters used was 200 and the feature selection being 40%. The test results on the test data provide an accuracy value of 96,074%, precision of 96,079%, recall of 96,074%, and an f-1 score of 96,070%.